2019
DOI: 10.1039/c8md00633d
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin alleviates the toxicity of graphene oxide for mammalian cells

Abstract: Toxicity of graphene oxide to cells reduced by almost 20% after its incubation with kaolin, most likely because of its adhesion to the platy clay nanoparticles, which was detected by atomic force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Indeed, the increase in the hydrodynamic diameter of the resulting coagulated kaolin–GO hybrid compared to pure kaolin or GO elucidated the aggregation of GO in the presence of kaolin particles. 27 The adsorption of GO nanosheets by kaolin particles and their consequent coagulation in aqueous environments was confirmed later in a study performed by Rozhina et al 28 Their results of AFM topography images coupled with the adhesion force maps of kaolin, GO, and kaolin–GO samples demonstrated the deposition of GO nanosheets onto the surface of kaolin particles. 28 Moreover, the interaction between kaolin and GO in aqueous environments was further investigated by Hoor et al 29 By comparison the FTIR spectra of kaolin, GO, and kaolin–GO hybrid, they declared that the adsorption of GO on the kaolinite particles was responsible for diminishing the original functional groups of kaolin such as O–H and Si–O and substituting them with the oxygen-containing functional groups of GO.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, the increase in the hydrodynamic diameter of the resulting coagulated kaolin–GO hybrid compared to pure kaolin or GO elucidated the aggregation of GO in the presence of kaolin particles. 27 The adsorption of GO nanosheets by kaolin particles and their consequent coagulation in aqueous environments was confirmed later in a study performed by Rozhina et al 28 Their results of AFM topography images coupled with the adhesion force maps of kaolin, GO, and kaolin–GO samples demonstrated the deposition of GO nanosheets onto the surface of kaolin particles. 28 Moreover, the interaction between kaolin and GO in aqueous environments was further investigated by Hoor et al 29 By comparison the FTIR spectra of kaolin, GO, and kaolin–GO hybrid, they declared that the adsorption of GO on the kaolinite particles was responsible for diminishing the original functional groups of kaolin such as O–H and Si–O and substituting them with the oxygen-containing functional groups of GO.…”
Section: Introductionmentioning
confidence: 75%
“…27 The adsorption of GO nanosheets by kaolin particles and their consequent coagulation in aqueous environments was conrmed later in a study performed by Rozhina et al 28 Their results of AFM topography images coupled with the adhesion force maps of kaolin, GO, and kaolin-GO samples demonstrated the deposition of GO nanosheets onto the surface of kaolin particles. 28 Moreover, the interaction between kaolin and GO in aqueous environments was further investigated by Hoor et al 29 By comparison the FTIR spectra of kaolin, GO, and kaolin-GO hybrid, they declared that the adsorption of GO on the kaolinite particles was responsible for diminishing the original functional groups of kaolin such as O-H and Si-O and substituting them with the oxygencontaining functional groups of GO. Also, as compared to pure kaolinite suspensions, a shi in the magnitude of zeta potential of kaolinite-GO suspensions at all pH regions was found, which was mainly attributed to the adsorption mechanism of GO on kaolin.…”
Section: Introductionmentioning
confidence: 97%
“…In a non‐cancer cell model, the cytotoxicity of Kaol was evaluated by applying Kaol on rat dermal fibroblast (RDF) cells, and the study showed that Kaol did not have any toxic effect on RDF cells; moreover, it also reduced the toxic effect of graphene oxide, resulting in a significant decrease in the percentage of apoptotic cells. [ 138 ] Furthermore, in a human lymphocyte cytotoxicity assay, non‐toxicity of Kaol to human lymphocytes was observed at doses ranging from 3.9 to 125 µg mL −1 . In comparison, cell viability remained greater than 85% at doses ranging from 125 to 500 µg mL −1 , which proves that Kaol can be characterized as a biocompatibile material for healthy cells.…”
Section: Biosafety Evaluation Of Kaolmentioning
confidence: 99%
“…No significant effect of the shape of the tested NMs on their internalization and cytotoxicity was demonstrated [ 75 ]. In this context, it is logical that the joint application of GO and kaolin has been found to reduce the negative effects of GBNs (by almost 20%, most likely because of coagulation of the NPs with each other) [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%